Mechanism-based discovery of ligands that counteract inhibition of the nicotinic acetylcholine receptor by cocaine and MK-801 - Hess, George P. (The National Academy of Sciences, 2000)
Nicotinic acetylcholine receptors (AChR) belong to a family of proteins that form ligand-gated transmembrane ion channels. They are involved in the fast transmission of signals between cells and the control of intercellular communication in the nervous system. A variety of therapeutic agents and abused drugs, including cocaine, inhibit the AChR and monoamine transporters and interfere with nervous system function. Here we describe a mechanism-based approach to prevent this inhibition. We had previously developed presteady-state kinetic (transient kinetic) techniques, with microsecond-to-millisecond time resolutions, for investigations of reactions on cell surfaces that allow one to determine the effects of inhibitors not only on the channel-opening probability but also on the opening and closing rates of the AChR channel. The transient kinetic measurements led to two predictions. (i) Ligands that bind to a regulatory site on the closed-channel conformation of the AChR with higher affinity than to the site on the open-channel form shift the equilibrium toward the closed-channel form, thereby inhibiting the receptor. (ii) Ligands that bind to a regulatory site with an affinity for the open conformation equal to or higher than their affinity for the closed conformations are expected not to inhibit the receptor and to displace inhibitors. The identification of such ligands in a combinatorial library of RNA ligands is reported. The implication of this approach to other protein-mediated reactions in which an inhibitor changes the equilibrium between active and inactive conformations is discussed.